The two-phase Hell-Shaw flow: construction of an exact solution - Malaikah, K.R. (Zielona Góra: Uniwersytet Zielonogórski)
We consider a two-phase Hele-Shaw cell whether or not the gap thickness is time-dependent. We construct an exact solution in terms of the Schwarz function of the interface for the two-phase Hele-Shaw flow. The derivation is based upon the single-valued complex velocity potential instead of the multiple-valued complex potential. As a result, the construction is applicable to the case of the time-dependent gap. In addition, there is no need to introduce branch cuts in the computational domain. Furthermore, the interface evolution in a two-phase problem is closely linked to its counterpart in a one-phase problem.
Keywords: Laplace growth; Hele-Shaw cell; Schwarz function; free boundary problem